An epidemiological study of neuroendocrine tumours at tertiary hospitals in Bosnia and Herzegovina - Maja Konrad Čustović; Ermina Iljazović; Azra Sadiković; Zinaida Karasalihović (Medicinski glasnik, 2020)
Aim: Neuroendocrine neoplasms (NENs) are a heterogeneous group of tumours with varying clinical expression and behaviour. Because of indolent behaviour of NENs, reviewing and evaluation of epidemiological characteristics is a challenge. The aim of this study was to assess prevalence of NENs at tertiary hospitals considering age, gender, location, and grade. Methods: Electronic files were used for a retrospective assessment of the patients with NENs of the gastroenteropancreatic tract and bronchopulmonary system in tertiary hospitals in Bosnia and Herzegovina over the past 15 years (2005-2020). Results: Among 438 patients, 291(66.4%) were males and 147 (33.6%) females; the median age was 62 years. The lungs were the most frequent site, 304 (69.4%), followed by the pancreas, 22 (5.0%), colon, 14 (3.2%), stomach, 13 (2.9%), appendix, 13 (2.9%), rectum,11 (2.5%), small intestine, eight (1.8%) and gallbladder, one (0.2%). Metastases were most frequently found in the liver, 35 (8%) and lymph nodes, 15 (3.42%). Conclusion: The results were largely consistent with those in literature, including age, gender, location, and the degree of differentiation. Most metastases originated from high-grade tumours and greater impairment of the liver.
Keywords: epidemiology; incidence; neuroendocrine tumours; tertiary care centres